2019
DOI: 10.1177/2324709619828408
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Advanced Urethral Diverticular Adenocarcinoma and a Review of Treatment Modalities

Abstract: Female urethral diverticular cancer is a very rare entity with only around 100 cases reported so far in literature and accounts for <1% of all malignancies. In this article, we present a 47-year-old African American female with repeated hospital visits for urinary retention, hematuria, and urinary tract infections. Initial computed tomography imaging and cystoscopy was unremarkable except for a distended urinary bladder. Subsequent magnetic resonance imaging and corresponding cystoscopy eventually indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
0
3
0
5
Order By: Relevance
“…Limited evidence exists on the risk of cancer after acute urinary retention. Although several case reports have suggested that acute urinary retention can be the presenting sign of cancers other than prostate cancer, 23 24 25 26 27 28 29 30 no study has quantified this association. One study carried out at a hospital in the UK during 1979-80—before the era of prostate specific antigen—provided some evidence on the risk of cancer after acute urinary retention.…”
Section: Discussionmentioning
confidence: 99%
“…Limited evidence exists on the risk of cancer after acute urinary retention. Although several case reports have suggested that acute urinary retention can be the presenting sign of cancers other than prostate cancer, 23 24 25 26 27 28 29 30 no study has quantified this association. One study carried out at a hospital in the UK during 1979-80—before the era of prostate specific antigen—provided some evidence on the risk of cancer after acute urinary retention.…”
Section: Discussionmentioning
confidence: 99%
“…3 Others have revealed that a large urethral diverticulum or advanced urethral diverticular adenocarcinoma can be the cause of urinary retention. 4,5 However, no report has described a calculus within the female urethral diverticulum, as a cause of acute urinary retention. We encountered the case of a bedridden and uncommunicative woman who had acute urinary retention due to a calculus within a urethral diverticulum, successfully treated by transurethral lithotripsy.…”
Section: Introductionmentioning
confidence: 99%
“…A prior case report revealed that a calculus within a female urethral diverticulum causes prolonged lower urinary tract symptoms such as dysuria 3 . Others have revealed that a large urethral diverticulum or advanced urethral diverticular adenocarcinoma can be the cause of urinary retention 4,5 . However, no report has described a calculus within the female urethral diverticulum, as a cause of acute urinary retention.…”
Section: Introductionmentioning
confidence: 99%
“…O objetivo deste relato foi apresentar um caso de adenocarcinoma do tipo intestinal originado a partir de um divertículo uretral com evolução metastática. 1,2 RELATO DO CASO Mulher de 56 anos, hipertensa, sem histórico de câncer na família, vem encaminhada por formação cística na porção superior do canal vaginal e sintomas de urge incontinência. Foi realizada RM que evidenciou formação cística circunferencial em terço médio da uretra medindo 3,8 x 1,8 cm.…”
Section: Introductionunclassified